Did boninite originate from the heterogeneous mantle with recycled ancient slab?. (28th September 2017) - Umino, Susumu; Kanayama, Kyoko; Kitamura, Keitaro; Tamura, Akihiro; Ishizuka, Osamu; Senda, Ryoko; Arai, Shoji
Abstract: Boninites are widely distributed along the western margin of the Pacific Plate extruded during the incipient stage of the subduction zone development in the early Paleogene period. This paper discusses the genetic relationships of boninite and antecedent protoarc basalt magmas and demonstrates their recycled ancient slab origin based on the T–P conditions and Pb–Hf–Nd–Os isotopic modeling. Primitive melt inclusions in chrome spinel from Ogasawara and Guam islands show severely depleted high‐SiO2, MgO (high‐silica) and less depleted low‐SiO2, MgO (low‐silica and ultralow‐silica) boninitic compositions. The genetic conditions of 1 346 °C at 0.58 GPa and 1 292 °C at 0.69 GPa for the low‐ and ultralow‐silica boninite magmas lie on adiabatic melting paths of depleted mid‐ocean ridge basalt mantle with a potential temperature of 1 430 °C in Ogasawara and of 1 370 °C in Guam, respectively. This is consistent with the model that the low‐ and ultralow‐silica boninites were produced by remelting of the residue of the protoarc basalt during the forearc spreading immediately following the subduction initiation. In contrast, the genetic conditions of 1 428 °C and 0.96 GPa for the high‐silica boninite magma is reconciled with the ascent of more depleted harzburgitic source which pre‐existed below the Izu–Ogasawara–Mariana forearc region before the subduction started. Mixing calculations based on the Pb–Nd–Hf isotopic data for the Mariana protoarc basalt and boninites support the above remelting model for the (ultra)low‐silica boninite and the discrete harzburgite source for the high‐silica boninite. Yb–Os isotopic modeling of the high‐Si boninite source indicates 18–30 wt% melting of the primitive upper mantle at 1.5–1.7 Ga, whereas the source mantle of the protoarc basalt, the residue of which became the source of the (ultra)low‐Si boninite, experienced only 3.5–4.0 wt% melt depletion at 3.6–3.1 Ga, much earlier than the average depleted mid‐ocean ridge basalt mantle with similar degrees of melt depletion at 2.6–2.2 Ga. Abstract : The origin and genetic conditions of coexsisting high‐silica and low‐silica boninites from Izu–Ogasawara–Mariana forearcs are discussed. The source mantle of high‐silica boninite is a harzburgite residue after 18–30 wt% melting of primitive mantle at 1.5–1.7 Ga, whereas the source of protoarc basalt, the residue of which remelted to form low‐silica boninite, is lherzolite that experienced only 3.5–4.0 wt% melt depletion at 3.6–3.1 Ga, much earlier than the average depleted MORB mantle with similar degrees of melt depletion at 2.6–2.2 Ga.